Establishing the evaluation framework of Underground Public Space Quality Assessment (UPSQA) - Zhou, Jie (2021)
Evaluating and improving the quality of Underground Public Space has become more significant for urban public realm utilisation, particularly in high density built urban areas. There is a necessity for a more scientific systematic evaluation approach to assess the quality of underground public places based on users' experience. Current literature shows that assessment criteria for traditional surface public places have a major impact on underground spatial design. However, an integrated research approach to debating the fundamental elements and key factors of underground public space is needed. Hence, this thesis aims to explore the key theories and practical cases to develop a matrix of qualitative assessment criteria for underground public places through a new research approach. 4 categories, 10 attributes, 46 indicators have been identified by SPSS Amos. Firstly, the fundamental philosophical hypothesis is proposed, including discussions on underground public space quality assessment methods. Secondly, the definition and advantages of mixed method design have been investigated. Thirdly, the rationality of the case study is summarised as a preferred method in this research. Finally, a pilot study is conducted on Beijing Yonganli Metro Station to verify the feasibility of the research method and adjust the study design for the proposed case study. Besides, specific assessment frameworks obtained by different methods have been compared and analysed side by side. This is also one of the analysis strategies adopted for the present study. In this research, Explore EFA (Exploratory Factor Analysis) and CFA (Confirmatory Factor Analysis) were used to rank and weight the indicators of the underground public space quality assessment system framework through literature review, professional interviews and three questionnaires. The analysis results of Chapter 5 to evaluate and score the design quality of underground public space around Guomao Station in the CBD area of Beijing have also been used. The author obtained three different results through three methods, and analysed and discussed the case results evaluated through the existing assessment criteria system. The research summarised a set of indicators of the quality evaluation system for the underground public space constructed and proposed the underground public space quality evaluation framework by analysing the design elements that affect underground space quality. Finally, the underground public space quality evaluation system has been applied and verified by taking the underground public space in Beijing's CBD area as an example. The final assessment results of the case indicated that people generally believe that high-quality places still have room for updates and improvements in the evaluation framework.